Koencim Q10 kot prehransko dopolnilo in zdravilo - Žmitek, Janko (Farmacevtski vestnik, 2009)
Coenzyme Q10 is a lipophilic compound playing an important role in the mitochondrial respiratory chain, where it acts as an electron carrier and as acarrier of proton transfer across membranes. It is also well known for its antioxidant properties. In the body CoQ10 mostly has an endogenous origin and is only partly derived by food. The biological role of CoQ10 is built on its redox equilibrium and continuous transformation between (oxidised) ubiquinone and (reduced) ubiquinol forms. Its function in the body is not affected by theform in which it is consumed. A decline in CoQ10 levels can be observed with increasing age, especially in the most active organs, while the beneficial effect of supplementation has been observed in many medical conditions. Due to its physical properties CoQ10 is very poorly absorbed from the gastrointestinal tract. Oil suspensions (soft-gel capsules) of ubiquinone and later ubiquionol represent the first important steps in increasing the bioavailability, while a further breakthrough was achieved with the development of water-soluble forms. An overview of CoQ10 products available onthe Slovenian market is presented.
Keywords: biodostopnost; koencim Q10; ubikinon